1980
DOI: 10.1126/science.210.4474.1081
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Laser Radiation Pressure

Abstract: Use of lasers has revolutionized the study and applications of radiation pressure. Light forces have been achieved which strongly affect the dynamics of individual small particles. It is now possible to optically accelerate, slow, stably trap, and manipulate micrometer-sized dielectric particles and atoms. This leads to a diversity of new scientific and practical applications in fields where small particles play a role, such as light scattering, cloud physics, aerosol science, atomic physics, quantum optics, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
286
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(290 citation statements)
references
References 51 publications
1
286
0
3
Order By: Relevance
“…spectroscopy [15,16]), the laser soon became a tool to actively manipulate and control atomic-scale matter. The work of Ashkin and colleagues in the 1970's [17,18] showed that the radiation pressure from a focused laser beam could be used to trap and move small (wavelength-scale) electrically neutral particles 1.2 . Closely related techniques to cool and eventually stop atoms were proposed [21,22], and demonstrated [23] in the same decade.…”
Section: Precise Position Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…spectroscopy [15,16]), the laser soon became a tool to actively manipulate and control atomic-scale matter. The work of Ashkin and colleagues in the 1970's [17,18] showed that the radiation pressure from a focused laser beam could be used to trap and move small (wavelength-scale) electrically neutral particles 1.2 . Closely related techniques to cool and eventually stop atoms were proposed [21,22], and demonstrated [23] in the same decade.…”
Section: Precise Position Measurementsmentioning
confidence: 99%
“…However due to their small transverse dimensions (∼ 10 − 100 nm), the nanobeam geometry does not have a large cross-section for electromagnetic scattering, making them not susceptible to scattering type [18] radiation pressure forces. Therefore, their interaction with optical cavity fields is mediated by gradient type forces [49,227,[229][230][231][232].…”
Section: Stressed Nanostring Coupled To An Optical Microcavitymentioning
confidence: 99%
“…Lower strain (<10% deformation) methods including optical stretchers (7,32) can apply non-destructive, non-contact forces sufficient to differentiate cell states (9,33,34). Optical stretching relies on the changing momentum of laser light by refraction at the surface of a soft dielectric object, generating non-contact optical forces (35). In specific laser configurations (36,37) and when operated at powers that minimize heating from optical absorption (38,39), these forces can deform trapped cells.…”
Section: Introductionmentioning
confidence: 99%
“…Optical tweezers have been widely used for manipulation of micro-or nano-size particles for physical, chemical, and or biological characterization [33][34][35]. The opticaltweezers technique is often combined with another technique, e.g., Raman spectroscopy, to make optical tweezersRaman spectroscopy, to further broaden its application in many research fields [36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%